Piloting forensic tele-mental health evaluations of asylum seekers - Green, Aliza S. (Psychiatry Res, 2020)
While the number of medical human rights programs has increased, there is substantial unmet need for forensic evaluations among asylum seekers throughout the United States. From September 2019 through May 2020, the Mount Sinai Human Rights Program has coordinated pro bono forensic mental health evaluations by telephone or video for individuals seeking protected immigration status who are unable to access in-person services. The national network clinicians conducted 32 forensic evaluations of individuals in eight U.S. states and Mexico seeking immigration relief. Remote forensic services have been a relevant solution for individuals in immigration detention, particularly during the COVID-19 pandemic.